2021
DOI: 10.1016/j.jep.2020.113264
|View full text |Cite
|
Sign up to set email alerts
|

The Herba Patriniae (Caprifoliaceae): A review on traditional uses, phytochemistry, pharmacology and quality control

Abstract: Ethnopharmacological relevance Herba Patriniae has been used for thousands of years in China as a traditional Chinese medicine with heat-clearing and detoxicating effects. It is applied widly for the treatment of rheumatoid arthritis, diarrhea, acute hepatitis, pelvic inflammatory disease and ulcerative colitis in clinic. Two species, namely Patrinia scabiosaefolia Fisch. ( PS ) and Patrinia villosa Juss. ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 68 publications
1
18
0
Order By: Relevance
“…As an important source of iridoids, Patrinia scabiosifolia Link, a perennial plant belonging to the Caprifoliaceae family, is distributed widely in East Asia including China, Japan, and North Korea [ 12 ]. The whole plants of P. scabiosifolia have been used as traditional Chinese medicine to treat appendicitis, diarrhea, and postpartum abdominal pain [ 13 ]. Previous phytochemical investigations on P. scabiosifolia led to the isolation of triterpenoids [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ], iridoids [ 21 , 22 , 23 , 24 , 25 ], flavonoids [ 21 ], and lignans [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…As an important source of iridoids, Patrinia scabiosifolia Link, a perennial plant belonging to the Caprifoliaceae family, is distributed widely in East Asia including China, Japan, and North Korea [ 12 ]. The whole plants of P. scabiosifolia have been used as traditional Chinese medicine to treat appendicitis, diarrhea, and postpartum abdominal pain [ 13 ]. Previous phytochemical investigations on P. scabiosifolia led to the isolation of triterpenoids [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ], iridoids [ 21 , 22 , 23 , 24 , 25 ], flavonoids [ 21 ], and lignans [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the authors did not specify the species of Herba patriniae in this study. Additionally, the mild side effects including temporary leukopenia, dizziness and nausea could be found in the patients treated with inappropriate dose of Herba Patriniae (Gong et al, 2021). As mentioned earlier, sodium houttuyfonate from H. cordata Thunb.…”
Section: Inhibition Of Biofilmmentioning
confidence: 85%
“…Herba patriniae, also known as Bai Jiang Cao, is a TCM for heat-clearing and detoxication, consisting of two species of Caprifoliaceae family, Patrinia scabiosifolia Link (Caprifoliaceae) and Patrinia villosa Juss. (Caprifoliaceae) (Gong et al, 2021). Fu et al reported that the water extract of Herba patriniae was able to disrupt the biofilm formation and alter the biofilm structure of P. aeruginosa PAO1 through inhibition of exopolysaccharide production and biofilmassociated genes including algU, pslM, pelA, algA, and bdlA (Fu et al, 2017).…”
Section: Inhibition Of Biofilmmentioning
confidence: 99%
“…Herba Patriniae consists of around 20 Patrinia species that were firstly recorded in “Shen Nong’s Herbal Classic” as medicinal materials. They are widely distributed in Eastern Asia and North America [ 6 ]. Ten species, three sub-species, and two variant species of the genus Patrinia have been used as medicinal herbs, which are grown in the eastern, central, southern, and southwestern regions of China, such as Patrinia scabiosaefolia , Patrinia villosa , Patrinia heterophylla , Patrinia rupestris , and Patrinia scabra [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ten species, three sub-species, and two variant species of the genus Patrinia have been used as medicinal herbs, which are grown in the eastern, central, southern, and southwestern regions of China, such as Patrinia scabiosaefolia , Patrinia villosa , Patrinia heterophylla , Patrinia rupestris , and Patrinia scabra [ 7 ]. As a folk herbal remedy, Herba Patriniae has long been used for clearing heat, detoxification, dispelling blood stasis, and relieving pain [ 6 ]. Modern pharmacological studies have reported that Herba Patriniae possesses potent antioxidant, anti-inflammation, and sedation properties [ 6 ].…”
Section: Introductionmentioning
confidence: 99%